Care of the Newborn : a Handbook for Primary Care. - Hertz, David E. (Wolters Kluwer Health, 2011)
This handbook is a comprehensive, concise, and accessible guide to the care of newborn infants, both healthy and ill. It provides the essential core of practical knowledge that pediatricians, family practitioners, residents, neonatal nurse practitioners, and medical students need to deliver optimal care to all neonates. The book can be easily read during a one-month neonatal rotation and used for quick reference. Normal newborn care, neonatal disease processes, and neonatal procedures are discussed and illustrated in a straightforward manner. The appendix provides a newborn formulary. The book.